Alu‐Alu mediated intragenic duplications in IFT81 and MATN3 are associated with skeletal dysplasias. Issue 10 (22nd August 2018) - Pettersson, Maria; Vaz, Raquel; Hammarsjö, Anna; Eisfeldt, Jesper; Carvalho, Claudia M.B.; Hofmeister, Wolfgang; Tham, Emma; Horemuzova, Eva; Voss, Ulrika; Nishimura, Gen; Klintberg, Bo; Nordgren, Ann; et al.
Abstract: Skeletal dysplasias are a diverse group of rare Mendelian disorders with clinical and genetic heterogeneity. Here, we used targeted copy number variant (CNV) screening and identified intragenic exonic duplications, formed through Alu‐Alu fusion events, in two individuals with skeletal dysplasia and negative exome sequencing results. First, we detected a homozygous tandem duplication of exon 9 and 10 in IFT81 in a boy with Jeune syndrome, or short‐rib thoracic dysplasia (SRTD) (MIM# 208500). Western blot analysis did not detect any wild‐type IFT81 protein in fibroblasts from the patient with the IFT81 duplication, but only a shorter isoform of IFT81 that was also present in the normal control samples. Complementary zebrafish studies suggested that loss of full‐length IFT81 protein but expression of a shorter form of IFT81 protein affects the phenotype while being compatible with life. Second, a de novo tandem duplication of exons 2 to 5 in MATN3 was identified in a girl with multiple epiphyseal dysplasia (MED) type 5 (MIM# 607078). Our data highlights the importance of detection and careful characterization of intragenic duplication CNVs, presenting them as a novel and very rare genetic mechanism in IFT81 ‐related Jeune syndrome and MATN3 ‐related MED. Abstract : We used targeted array and WGS to detect and characterize Alu‐Alu mediated intragenic duplications in two individuals with distinct skeletal dysplasias, Jeune syndrome and multiple epiphyseal dysplasia (MED) type 5. The homozygous IFT81 duplication was inherited from heterozygous, unaffected parents and the heterozygous MATN3 duplication had arisen de novo . Studies in primary cells and zebrafish showed that the IFT81 duplication results in loss of a specific splice isoform, highlighting the importance of transcript‐specific mutations in the pathogenesis of rare diseases.